ОЦІНКА СТАНУ ЗАБРУДНЕННЯ ДОННИХ ОСАДОК ВАЖКИМИ МЕТАЛАМИ В ПРИБЕРЕЖНИХ РАЙОНАХ КРИМУ (ЧОРНЕ МОРЕ) - Губанов, В. І.; Копитов, Ю. П.; Бобко, Н. І. (Marine Ecological Journal, 2023)
The paper presents results of definition of heavy metals concentrations (Pb, Cd, Cu, Zn, Ni, Hg, Cr) in a surface layer of bottom sediments in coastal waters of Crimea. Comparison of heavy metals in the regions with their concentrations in open areas of the Black Sea, with their natural clarkes in lithosphere and permissible levels of polluting substances on "the Dutch sheets" is spent. Values are calculated of factors and indexes of degree of heavy metals pollution in bottom sediments.